Pharmacological actions of bacuri butter (Platonia insignis Mart.): an integrative review - José Francisco Ribeiro; Maria do Livramento Fortes Figueiredo; André Luís Menezes Carvalho; Benedito Pereira de Sousa Neto (Universidade Federal do Ceará, 2021)
Objective: to identify the pharmacological activities of bacuri butter (Platonia insignis Mart.). Methods: an integrative review, carried out in the databases of Latin American and Caribbean Literature in Health Sciences, Cumulative Index to Nursing and Allied Health Literature, EMBASE, MEDLINE/PubMed, Web of Science, Cochrane Library and SCOPUS, without the time and language restriction. The selection consisted of 13 pre-clinical trials. The information assessment descriptively took place, comparing with the pertinent findings. Results: it was observed that 50.0% of the publications were indexed in MEDLINE/PubMed, most publications were from England (61.5%), followed by Brazil and the United States, both with 13.3%. It is noteworthy that 100.0% of the articles were pre-clinical trials; pharmacological activities for antioxidants (38.4%) and antileishmanicides (30.7%). It was found that 38.4% of the trials presented toxicity tests. Conclusion: bacuri butter (Platonia insignis Mart.) Showed pharmacological activities in pre-clinical trials, such as antioxidants, antileshimaniasis, anticonvulsant and wound healing.